S6.5d Molecular identification of mycetoma causative agents from patients in ahospital setting in Senegal. (20th September 2022) - Sow, Doudou; Deh, Aminata; Minlékib, Carole Pab; Ndiaye, Maodo; Manga, Isaac; Lelo, Souleye; Fall, Cheikh Bintou; Sylla, Khadime; Ndiaye, Magatte; Tine, Roger; Dieng, Thérèse; Faye, Babacar
Abstract: S6.5 Efforts of improving the management of mycetoma: working towards the 2030 goals, September 22, 2022, 4:45 PM - 6:15 PM:   Background: Mycetoma is a chronic granulomatous inflammatory disease that is caused either by bacteria or fungi. The diagnosis of species is important to guide the therapeutic management of patients particularly for white and yellow grains. However, the identification of the causative agents using mycological and histological techniques is a real problem in our countries. This study aims to identify etiologic agents using molecular techniques in Senegal. Methods: A prospective study was carried out to compare mycological and histological techniques with molecular methods in patients attending hospital settings. Biopsy specimens and/or grains obtained from these patients were examined by PCR targeting the ITS (fungal agents) and 16S (actinomycosis agents) genes. Sequencing with the SANGER method allowed us to identify the species. Results: Preliminary results were obtained from 30 patients. The grains collected were black (38%), red (4.7%), white (47.6%), and yellow (9.5%). Discriminative PCR ITS vs 16S identified 5 actinomycosis agents including white and yellow grains and 1 fungal agent. The fungal agent was identified after sequencing as Microsporum langeronii . Conclusion: The preliminary results of this study show the importance of discriminative PCR to guide the therapeutic choice of clinicians. Its widespread use could improve the detection and management of mycetoma cases in Senegal.